The secret life of pets - Renaud, Chris; Cheney, Yarrow; Paul, Cinco; C. K., Louis; Stonestreet, Eric, 1971-; Hart, Kevin, 1979-; Slate, Jenny, 1982-; Kemper, Ellie, 1980-; Brooks, Albert, 1947-; Bell, Lake, 1979-; Carvey, Dana; Buress, Hannibal; et al. ([Universal City, California] : Universal Studios Home Entertainment, 2016)
A hilarious comedy about the lives our pets lead after we leave for work or school each day. Max, a terrier, has his favorite-pet status turned upside down when his owner takes in a stray named Duke.
Originally part of a Blu-ray + DVD combo pack.
Title from disc label.
Originally released as a motion picture in 2016.
Bonus features: 3 mini-movies; All about the pets; Animals can talk: Meet the actors; Hairstylist to the dogs; The best of Snowball and more.
Director, Yarrow Cheney, Chris Renaud.
Voices of: Louis C.K., Eric Stonestreet, Kevin Hart, Jenny Slate, Ellie Kemper, Albert Brooks, Lake Bell, Dana Carvey, Hannibal Buress, Chris Renaud, Steve Coogan, Sandra Echeverria, Jaime Camil.
Keywords: Pets -- Juvenile drama; Manhattan (New York, N.Y.) -- Juvenile drama; New York (N.Y.) -- Manhattan -- Juvenile drama; Video recordings for the hearing impaired; Feature films; Children's films; Comedy films; Action and adventure films; Animated films; Family films